Analisis Manajemen Risiko Teknologi Informasi dengan ISO 31000 pada Aplikasi Ayo SRC - Rohmat, Deni Rohmat (LPPM & Fakultas Teknologi Informasi UNSAP, 2024)
ABSTRACT The development of technology is currently very fast and rapid so that technology becomes a very intimate need in everyday life, especially in the business world. But from all that there must be a risk that arises. Risk (risk) is the effect of uncertainty on a goal. Influence is a deviation from the expected result, the result can be positive, negative or both so that it can overcome, create or generate opportunities and threats. Toko Komar is a wholesaler that already uses the application of information technology to support its business activities. The store uses the Ayo SRC application which is used to support sales, record inventory, and record daily expenses needed. However, in the world of management, there are always possible risks that may occur and can disrupt business activities in using the system. That way risk analysis is needed for the resources contained in the store. Using ISO 31000 is expected to minimize the risks contained in the Ayo SRC application. The results of this risk analysis are in the form of an analysis of possible risks, grouping possible risks based on their impact so as to produce risk action proposals for possible risks contained in the Ayo SRC application, so that the store can treat possible risks according to the priority level of risk and can prevent and minimize so as not to disrupt business activities.